Factors which influence the length of an out-of-hours telephone consultation in primary care: a retrospective database study - Mohammed Mohammed A; Clements Gill; Edwards Elaine; Lester Helen (BMC, 2012)
Abstract Background Given the increasing use of telephone consultation it is important to determine the factors which influence the length of a telephone consultation. Method Analysis of 128717 telephone consultations during January to December 2011 to a National Health Service (NHS) out-of-hours primary care service provider in Shropshire and Telford and Powys, England, involving 102 General Practitioners (GPs) and 36 Nurse Practitioners (NPs). Telephone consultation conclude with one of three outcomes - advice only, the patient is invited to a face-to-face consultation with a GP or NP at a nearby health centre (known as a base visit) or the patient is visited at home by a GP or NP (known as home visit). Call length was analysed by these outcomes. Results The overall mean call length was 7.78 minutes (standard deviation (SD) 4.77). Calls for advice only were longest (mean 8.11 minutes, SD 5.17), followed by calls which concluded with a base visit (mean 7.36 minutes, SD 4.08) or a home visit (mean 7.16 minutes, SD 4.53). Two primary factors influenced call length. Calls by GPs were shorter (mean 7.15 minutes, SD 4.41) than those by NPs (mean 8.74 minutes, SD 5.31) and calls designated as a mental health call were longer (mean 11.16 minutes, SD 4.75) than all other calls (mean 7.73 minutes, SD 7.7). Conclusions Telephone consultation length in the out-of-hours setting is influenced primarily by whether the clinician is a GP or a NP and whether the call is designated as a mental health call or not. These findings suggest that appropriate attempts to reduce the length of the telephone consultations should focus on these two areas, although the longer consultation length associated with NPs is offset to some extent by their lower employment costs compared to GPs. Nonetheless the extent to which the length of a telephone consultation impacts on subsequent use of the health service and correlates with quality and safety remains unclear.